Microwave Absorption Properties of Ceramics Based on BiFeO3 Modified with Ho - Pavel Astafev; Konstantin Andryushin; Aleksey Pavelko; Alexander Lerer; Yakov Reizenkind; Ekaterina Glazunova; Lidiya Shilkina; Inna Andryushina; Alexandr Nagaenko; Larisa Reznichenko (Solids, 2024)
Ceramic samples of Bi1−xHoxFeO3, where x = 0.00–0.50, with a modifier concentration variation step ∆x = 0.05–0.10, were prepared by a two-step solid-phase synthesis followed by sintering using conventional ceramic technology. X-ray phase analysis showed that all the solid solutions studied were formed in the presence of impurities. With increasing Ho concentration, a non-monotonic shift in all loss maxima towards the low-frequency region is observed, as well as an increase in their half-width. An increase in the external temperature leads to a monotonic shift in the absorption maxima towards the low-frequency region, which enables the necessary control of the microwave parameters in the X band. A conclusion has been drawn on the feasibility of using the data obtained in the design of new functional materials based on BiFeO3, as well as devices with thermally controlled frequency.